A New Wave of Talent: Big 4 Response to New Partner Qualification Requirements in China - Bianchi, Pietro A.; Liao, Lin; Minutti-Meza, Miguel; Wang, Yini (The Accounting Review, 2026)
ABSTRACT We examine how the Big 4 responded to evolving partner qualification requirements in China. By 2017, at least 80 percent of the Big 4 partners were required to hold CICPA qualifications, a requirement that did not apply to local firms. Using data from a 14-year window around the reform, we document that the Big 4 expanded their partnership and primarily complied through internal promotion of locally licensed auditors, often into junior signing roles and serving new clients. Our analyses of audit outcomes yield mixed and time-varying evidence: although we observe relative increases in restatements in selected periods, the triangulated evidence does not suggest a pervasive deterioration in audit quality. However, we find a decline in the Big 4’s market share and audit fee premium. Overall, our findings shed light on how regulatory interventions targeting auditor qualifications reshape audit firms and market competition. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M4; M40; M41; M42; M49.